2010
DOI: 10.15809/irriga.2010v15n4p353
|View full text |Cite
|
Sign up to set email alerts
|

Doses De Nitrogênio Na Produção De Rabanete Fertirrigado E Determinação De Clorofila Por Medidor Portátil Nas Folhas

Abstract: A determinação do teor relativo de clorofila por meio do clorofilômetro é utilizada para predizer a necessidade de adubação nitrogenada visando incrementar a produção em várias culturas. Este trabalho objetivou avaliar a resposta de doses de nitrogênio adicionadas ao solo via fertirrigação na produção de rabanete e a relação de clorofila com o teor de nitrogênio foliar da cultivar Redondo Vermelho. O delineamento experimental foram blocos casualizados, com cinco tratamentos (0; 30; 60; 120; 240 kg N ha -1 ) , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
5
2
5
Order By: Relevance
“…These results differ from those obtained by Quadros et al (2010), who also worked with radish and N doses applied by fertigation, since they found that the doses of N did not interfere with the production of radish.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…These results differ from those obtained by Quadros et al (2010), who also worked with radish and N doses applied by fertigation, since they found that the doses of N did not interfere with the production of radish.…”
Section: Resultscontrasting
confidence: 99%
“…The deficiency of this nutrient may be responsible for reducing the quantity of assimilated generated during the carbon dioxide fixation process, reducing the availability of these compounds for reproductive organs. Although nitrogen is an important nutrient for vegetables, little is known about the amounts to be used in the radish crop (Quadros et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entretanto, guardadas as devidas diferenças entre as duas culturas, ambas apresentam uma resposta similar à adição de N à cultura. Já Quadros et al (2010), avaliando adubação nitrogenada na cultura do rabanete, não constataram efeito significativo para essa variável.…”
Section: Figuraunclassified
“…Some soil-and plant-based nutrient management practices have been used to enhance radish yield and NUE. Examples include leaf color charts and chlorophyll meters, which generally Establishment and Validation of Nutrient Expert System for Radish Fertilization Management in China provide real-time guidance for the topdressing application of N fertilizer for crops (Westerveld, 2004;Quadros et al, 2010). Soil testing has been encouraged and used to develop nutrient recommendations in China He et al, 2009;Song and Yi, 2011).…”
mentioning
confidence: 99%